STRATEGI BERTAHAN DAN PROMOSI UMKM DIMASA PANDEMI COVID 19 (STUDI KASUS PADA BATIK MELAYU PINANG SIRIH KOTA PANGKALPINANG) - Rahmad Firdaus (LPPM STIE PERTIBA Pangkalpinang, 2021)
The global Covid-19 pandemic certainly has an impact on various sectors, especially in the economic sector. The COVID-19 pandemic has had a considerable impact on various sectors in Indonesia, especially in the MSME sector. The corona outbreak that has become increasingly massive lately has finally disrupted the decline in sales and marketing processes. For this reason, a survival and promotion strategy is needed for MSMEs to be able to continue to maintain their business and keep abreast of business developments during this COVID-19 pandemic. The object of this research is the UMKM Batik Melayu Pinang Sirih Pangkalpinang City. The research methodology in this study is qualitative research with participatory observation data collection techniques with exploratory steps, namely doing one of the recommended qualitative data collection techniques to obtain descriptive data. The results of this study are so that MSMEs can survive in the face of the covid-19 pandemic, they can open new product lines and innovate to make new products following developments during the covid-19 pandemic or in the future as was done by Batik Malayu Pinang Sirih, namely producing cloth masks, bag, and headmaster. In addition, they can survive in carrying out promotional strategies using digital marketing and customer relationship marketing.